2017
DOI: 10.1155/2017/9417350
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Pet Ownership with Older Adults Eating Patterns and Health

Abstract: Pet ownership has been shown to improve quality of life for older adults. The objective of this cross-sectional study was to compare older pet owners and older non-pet owners and assess differences between groups. This study was conducted on adults over 50 years of age, who owned either one cat or one dog versus nonowners based on age, race, gender, and education. Matched older pet owners (OPO) versus non-pet owners (NPO) pairs (n = 84), older cat owners (OCO) versus non-cat owners (NCO) (n = 29), and older do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Although the positive association between dog ownership and physical activity has been discussed previously, the association between pet ownership and dietary habits has not been extensively assessed. To our knowledge, only the study by Heuberger et al 34 reported differences in eating patterns among older adults owning or not owning a dog. How pet ownership may favor a healthier diet is yet to be determined.…”
Section: Discussionmentioning
confidence: 91%
“…Although the positive association between dog ownership and physical activity has been discussed previously, the association between pet ownership and dietary habits has not been extensively assessed. To our knowledge, only the study by Heuberger et al 34 reported differences in eating patterns among older adults owning or not owning a dog. How pet ownership may favor a healthier diet is yet to be determined.…”
Section: Discussionmentioning
confidence: 91%
“…In studies utilizing activity monitors, adults ≥55 years of age walked their dogs for an average of 30 min per day (moderate-vigorous physical activity) [6] and adults ≥65 years of age spent more time walking at a moderate cadence compared to nonowners [7]. Older dog owners (>50 years) were shown to have lower BMI, fewer medical diagnoses, and used fewer prescription medications compared to age-matched nonowners [8]; activity was not taken into consideration. A meta-analysis study in older adults (>50 years) provided evidence that dog walking, and not dog ownership per se, is the mechanism by which dog ownership promotes health, including lower BMI, fewer activities of daily living limitations, and fewer doctor visits [9].…”
Section: Introductionmentioning
confidence: 99%
“…In studies concerning pet ownership, researchers have demonstrated that pets in the home increase elders’ well-being and physical health, as well as health behaviors. Pet ownership is associated with fewer health problems, fewer prescription medications, lower stress, and improved pain relief ( Heuberger, 2017 ; Ogechi et al, 2016 ). Moreover, pet ownership is related to improved quality of life through increased stimulation of oxytocin, an increased sense of purpose in life, and decreased loneliness ( Wells, 2019 ).…”
Section: Using One Health To Understand Urban Aging: Evidence From Al...mentioning
confidence: 99%